1989
DOI: 10.1088/0031-8949/39/5/029
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated oxidation of Fe2+(aq): a Mars simulation experiment studied by Mössbauer spectroscopy

Abstract: It is generally believed that liquid water was once stable on the surface of Mars. In the rather thin and nearly oxygenfree atmosphere of Mars UV-radiation from the Sun reaches the martian surface, and in aqueous environment UV-light is a source of oxidation of Fe2+ (aq). As a Mars simulation experiment, we have studied the precipitates forming from the photochemical oxidation of Fe2+ (aq) in the laboratory by means of Mössbauer spectroscopy.Our results show that α-FeOOH (goethite) must have precipitated in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The reversible reaction of Fe 21 to Fe 31 occurs in the combined reaction, but not in the Fenton reaction, and would be useful for applying the technology to mineralization of triclosan in the field. Consequently, the combined Fe 21 and UV-C reaction is a promising method for the mineralization of triclosan and the induction of the reversible reaction between Fe 21 and Fe 31 . The combined (Fe 21 and UV-C) reaction can overcome the disadvantages of the Fenton reaction such as sludge production, the use of expensive H 2 O 2 , and pH adjustment, making the combined reaction more practical than the Fenton reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reversible reaction of Fe 21 to Fe 31 occurs in the combined reaction, but not in the Fenton reaction, and would be useful for applying the technology to mineralization of triclosan in the field. Consequently, the combined Fe 21 and UV-C reaction is a promising method for the mineralization of triclosan and the induction of the reversible reaction between Fe 21 and Fe 31 . The combined (Fe 21 and UV-C) reaction can overcome the disadvantages of the Fenton reaction such as sludge production, the use of expensive H 2 O 2 , and pH adjustment, making the combined reaction more practical than the Fenton reaction.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was not observed in the Fe 21 -only or Fenton reaction. Lundgreen et al [31] reported that the reduction of Fe 31 to Fe 21 occurred with UV irradiation at wavelengths less than 270 nm in the photolytic reaction. The increase of Fe 21 in the combined reaction indicates that the reduction of Fe 31 to Fe 21 (Eq.…”
Section: Oxidation Of Fe 21 In the Fenton And Combined Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of Fe III photo-reduction on Mars is rarely discussed in the astrobiology literature. Most researchers discuss Fe II photo-oxidation (Cairns-Smith 1978, and the later work of Braterman et al 1983;Borowska and Mauzerall 1986;Lundgreen et al 1989;Kim et al 2013). Short wave-length UV-C light (maximum at 267 nm; Kim et al 2013) in controlled laboratory experiments created Fe II photo-oxidation, as opposed to Fe III photo-reduction, which is induced by light over a wider range of wavelengths (200 to 450 nm, maximum at 300 nm, David and David 1976).…”
Section: Comparison Between Mineralogical Features Of Copahue-caviahumentioning
confidence: 99%
“…The Mössbauer characterization of pure iron-bearing solids allows to attribute a specific value of the hyperfine parameters to a given solid, and thus to various iron oxidation, spin state and coordination. As pure Fe(III) solid phases, we focused on natural lepidocrocite (c-FeOOH) (Huggins et al, 1983;Lundgreen et al, 1989;Sprenkel-Segel, 1970) and natural ferrihydrite (Childs and Johnston, 1980;Madsen et al, 1986), as well as corresponding synthetic samples. Lepidocrocite is synthesized in chloride medium whereas ferrihydrite is obtained from Fe(II) dissolved in carbonate and phosphate ionic medium (Benali et al, 2001;Cornell and Schwertmann, 2003;Génin et al, 2006).…”
Section: Structural Fe In Natural and Synthetic Materialsmentioning
confidence: 99%